HUBUNGAN MATH ANXIETY DAN COMPUTATIONAL THINKING TINJAUAN SISTEMATIS DALAM PERSPEKTIF HIGHER ORDER THINKING SKILLS - Nia Dahlia; Hepsi Nindiasari (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study is motivated by the importance of higher order thinking skills (HOTS) and computational thinking (CT) in 21st-century mathematics education, as well as the affective factor of mathematics anxiety that may influence these abilities. The purpose of this study is to examine the relationship between mathematics anxiety and computational thinking skills, and to analyze the role of HOTS within this relationship through a systematic literature review (SLR) approach. The method follows the PRISMA model, including identification, screening, eligibility assessment, and data synthesis stages, involving 15 articles indexed in Scopus and Sinta, retrieved from Google Scholar (6 Scopus-indexed and 9 Sinta 1-4 indexed articles) published between 2021 and 2026. The findings indicate that most studies show a negative relationship between mathematics anxiety and CT, where increased anxiety is associated with lower computational thinking ability. However, this relationship is contextual and influenced by technology-based and innovative learning interventions. Furthermore, CT acts as a mediating variable that can reduce the negative impact of anxiety on learning outcomes, while HOTS functions as a cognitive framework linking affective and cognitive aspects. These findings highlight the importance of integrating CT and HOTS in mathematics learning to enhance students’ thinking quality while minimizing mathematics anxiety.